The Great Syrian Revolt and the Rise of Arab Nationalism: By Michael Provence (Austin: University of Texas Press, 2005. 209 pages.) (American Journal of Islam and Society, 2006)
The more things change, the more they stay the same. Any reader of MichaelProvence’s study of the Great Syrian Revolt of 1925 might be forgiven suchcynicism. Here is a fine and well-documented example of an earlier attemptby a western power to come to grips with the Middle East – with unfortunateresults. It involved foreigners infallibly confident in themselves andtheir mission, compliant local elites out for self-aggrandizement, insurgentspreaching religious-inflected nationalism, the gulf between all three, and theensuing horror. The Great Syrian Revolt was a pivotal event both for Syriaand for Arabs at large. It allowed the former to conceptualize themselves asa nation while serving as an exemplar for the latter, thereby playing a formativerole in the development of national consciousness in the region. Byinfluencing the Baathist movement two decades later, it had ramificationsfar beyond its failure.Provence devotes much of the first chapter to staking out interesting theoreticalground. Rejecting the notion of insurrection as being largely a battleof ideas directed by intellectuals, he argues persuasively for an approachto the rebellion centered on a rural, rather than an urban, setting and for acasus belli founded on French misrule and economic relations between differingclasses of Syrian society. His central thesis is that the grain tradebetween the Druze in the fertile Hawran region of southern Syria andmiddle-class merchants, mostly from the Maydan quarter of Damascus, wasthe central axis upon which the revolt turned.Such an approach has its drawbacks, namely, the paucity of documentaryevidence from contemporary rural Syria. Much of the latter half of thefirst chapter is devoted to this difficulty. In casting a judicious eye over therange of primary source material, both French and Arabic, Provence ...